(untitled) (International Conference on Education, Psychology and Humanities, 2026)
The article analyzes the moral and aesthetic factors that ensure social stability in the personality of a leader, based on the Eastern philosophical tradition, specifically Confucianism, Islamic ethics, and the heritage of Central Asian thinkers. Concepts such as justice, governance, self-cultivation, and the ideal of beauty are examined through a philosophical-comparative method, and their relevance to modern leadership theory is substantiated.